Analysis of Public Perception on the Effectiveness of the Existence of Trans Padang Bus Transportation - Yusnaena Yusnaena; Mustika Lukman Arief; Syahrul Effendy (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to find out and analysis of public perception on the effectiveness of the existence of trans padang bus transportation. The population of this research is the people of Padang City who have used trans padang bus transportation services. Sampling in this study is conducted by accidental sampling method. Based on the results of the above calculations, the number of samples that will be used in this study is 96 respondents. The data collection method use in the study is using a questionnaire. The analysis used in this study is multiple linear regression. Multiple linear regression consists of partial test (t), simultaneous test (F), and coefficient of determination test (R2). The results show in partial test (t) that internal factor has a positive and significant effect on the effectiveness of the existence of trans padang bus transportation. External factor has a positive and significant effect on the effectiveness of the existence of trans padang bus transportation. Based on simultaneous test (F), internal and external factor simultaneously effect on the effectiveness of the existence of trans padang bus transportation. The results of coefficient of determination test (R2) show that value of r square is 0.828. This means that 82.8% of the effectiveness of the existence of trans padang bus transportation is influenced by internal and external factors. Of this amount, there is a remainder of 17.2% (100%-82.8%) influenced by other factors. As for what is meant by these other factors are factors that are not estimated or not taken into account in this study.